Atomic Force Microscopy in Microbiology: New Structural and Functional Insights into the Microbial Cell Surface - Yves F. Dufrêne (American Society for Microbiology, 2014)
ABSTRACT Microbial cells sense and respond to their environment using their surface constituents. Therefore, understanding the assembly and biophysical properties of cell surface molecules is an important research topic. With its ability to observe living microbial cells at nanometer resolution and to manipulate single-cell surface molecules, atomic force microscopy (AFM) has emerged as a powerful tool in microbiology. Here, we survey major breakthroughs made in cell surface microbiology using AFM techniques, emphasizing the most recent structural and functional insights.